A second species of the genus Martensolasma (Opiliones, Dyspnoi, Nemastomatidae) from Mexico - Cruz-López, Jesús A. (Zootaxa, 2017)
A second species of the previously monotypic genus Martensolasma Shear, 2006 is described: Martensolasma catrina sp. n., based on specimens collected in Metztitlán, Hidalgo, Mexico. The taxonomy the genus is briefly discussed.